Evaluasi Implementasi Standar Akuntansi Pemerintahan Berbasis Akrual pada Pemerintahan Provinsi Sumatera Utara - Raya Puspita Sari Hasibuan (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2018)
The aim of this research is to examine the evaluation of implementation government standard accounting accrual based. The sampling method of this research used census sampling, whether the sample of this research is 415 respondends. Samples of the research is Local Government Unit (SKPD) in the five district or city in North Sumatera, they are Langkat, Binjai, Medan, Samosir and Humbang Hasudutan. This research using SmartPLS application to analyse the data. The main problems is about how difficult government coordinate the human resource in the district or city government especially in implementation of accounting system. Methods of data analysis used in this research is testing the quality of the data, outer model and inner model test. Outer model consists of convergent validity, discriminant validity and reliability test and inner model consists of adjusted R square and Predictive Relevance (Q2). The result of this research is partially human resource, software and hardware and understanding of government standard accounting accrual based have effect to implementation government standard accounting accrual based.